Macrophages as Key Players during Adipose Tissue–Liver Crosstalk in Nonalcoholic Fatty Liver Disease - Korf, Hannelie; Boesch, Markus; Meelberghs, Lore; van der Merwe, Schalk (Seminars in Liver Disease, 2019)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in Western countries that could lead to serious health problems including liver failure, cancer, or death. The term NAFLD includes a spectrum of disease states with histological features ranging from simple steatosis to nonalcoholic steatohepatitis (NASH). A key aspect within this research field is the identification of pathogenic factors that trigger inflammation, thus fueling the transition from nonalcoholic fatty liver to NASH. These inflammatory triggers may originate from within the liver as a result of innate immune cell activation and/or hepatocyte injury. Additionally, they may originate from other sites such as adipose tissue or the intestinal tract. In the current review, the authors will primarily focus on events within adipose tissue which may be of importance in triggering the disease progression. They specifically focus on the role of adipose tissue macrophages during NAFLD pathogenesis and how microenvironmental factors may shape their metabolic profile. They further dissect how redirecting the macrophage's metabolic profile alters their immunological functions. Finally, they discuss the opportunities and challenges of targeting macrophages to interfere in disease progression.
Keywords: nonalcoholic fatty liver disease; macrophages; adipose tissue inflammation; metabolism